2016
DOI: 10.1088/0029-5515/56/6/066002
|View full text |Cite
|
Sign up to set email alerts
|

The role of MHD in causing impurity peaking in JET hybrid plasmas

Abstract: In Hybrid plasma operation in JET with its ITER-like wall (JET-ILW) it is found that n>1 tearing activity can significantly enhance the rate of on-axis peaking of tungsten impurities, which in turn significantly degrades discharge performance. Core n=1 instabilities can be beneficial in removing tungsten impurities from the plasma core (e.g. sawteeth or fishbones), but can conversely also degrade core confinement (particularly in combination with simultaneous n=3 activity). The nature of MHD instabilities in J… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
47
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 41 publications
1
47
0
1
Order By: Relevance
“…Central radio frequency (RF) heating has been identified as a reliable method to limit the central concentration of heavy impurities [1][2][3][4][5][6][7][8][9]. Since the behaviour and the profile shapes of heavy impurities are determined by both turbulent [10][11][12][13][14][15][16][17][18][19][20][21][22][23] and neoclassical transport [25][26][27][28][29][30], and are also affected by the presence of magneto-hydrodynamic (MHD) instabilities [6,[31][32][33][34][35], the physics behind the reduction of the central peaking of the W density produced by central RF heating can be expected to involve a certain level of complexity, in which multiple effects are combined. Central RF heating not only modifies the temperature, density and rotation profiles of the main plasma, but can also directly modify the impurity transport.…”
Section: Introductionmentioning
confidence: 99%
“…Central radio frequency (RF) heating has been identified as a reliable method to limit the central concentration of heavy impurities [1][2][3][4][5][6][7][8][9]. Since the behaviour and the profile shapes of heavy impurities are determined by both turbulent [10][11][12][13][14][15][16][17][18][19][20][21][22][23] and neoclassical transport [25][26][27][28][29][30], and are also affected by the presence of magneto-hydrodynamic (MHD) instabilities [6,[31][32][33][34][35], the physics behind the reduction of the central peaking of the W density produced by central RF heating can be expected to involve a certain level of complexity, in which multiple effects are combined. Central RF heating not only modifies the temperature, density and rotation profiles of the main plasma, but can also directly modify the impurity transport.…”
Section: Introductionmentioning
confidence: 99%
“…Another concern related to magnetic islands is their potential to favour the inward transport of heavy impurities like tungsten towards the core plasma. This effect has been observed experimentally 30,31 and it is again attributed to the interplay of magnetic island, turbulence and neoclassical physics. Hender 30 argues that the temperature flattening inside the island on the one hand increases the neoclassical inward convection of tungsten and on the other hand decreases the diffusivity due to ITG turbulence.…”
Section: Introductionmentioning
confidence: 55%
“…In addition, magneto-hydrodynamic (MHD) instabilities such as tearing modes and sawtooth oscillations add complexity to the impurity behaviour in core plasmas. Indeed, it is observed that the presence of tearing modes locally increases the impurity diffusivity in the islands and enhances accumulation [18]. Also, discrepancies are found between the measured impurity behaviour in presence of the internal kink mode and the neoclassical and turbulent predictions [19].…”
Section: Introductionmentioning
confidence: 97%